Idea „ekonomii przyrody ożywionej” jako próba wyjaśnienia jej jedności, harmonii, ciągłości i stabilności - Pietrzak, Zbigniew (Humaniora. Czasopismo Internetowe, 2023)
Attempts to explain the “phenomenon” of the stability and unity of nature were the subject of philosophical reflections and then of natural science research. The purpose of formulated concepts was to capture and describe the mechanisms of the perceived harmony of nature, for instance, in archaic myths personifying nature or in ancient Ionian philosophy. In modern times, these ideas were expressed in the form of a principle analogous to the contemporary “energy conservation law” and “the chain of being,” and finally they were covered in Linnaeus’s work under the common name “oeconomia naturae.” These ideas were reformulated by Darwin in his theory in which he concluded that this stability and harmony can be described using the term “economy of nature.” Such an approach to natural phenomena, allowing observation of new relationships between various elements of nature, made it possible to mathematize the sciences of animate nature. Changes in the perception of nature (philosophy of nature) had their consequences in the methodology of the natural sciences. Darwin’s theory reinterprets all earlier ideas, reducing their sense to the balance between costs and benefits, losses and profits. The contents of the article focus on discussing the concepts of Linnaeus and Darwin, treating previous ideas as introduction to the actual issues.